REFORMS IN UZBEKISTAN EFFECT ON THE FAMILY ENVIRONMENT - Aziza Turayeva Pulatovna (American Journals Publishing, 2023)
The article discusses the impact of economic, political-legal, social and spiritual-cultural reforms on the family environment in Uzbekistan.
Keywords: family, family environment, improvement of family environment, reform, economic processes, political-legal processes, social processes, spiritual-cultural processes.